PENGARUH LATIHAN KESEIMBANGAN METODE VLADIMIR JANDA TERHADAP RISIKO CEDERA OLAHRAGA BASKET PADA PELAJAR LAKI-LAKI SMP NEGERI 15 MEDAN - Nondang Purnama Siregar; Santosa Santosa; Nur Arfian (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
The incidence of injuries in the sport of basketball was ranked third after football and handball. Basketball is the learning materials required in junior high school through the physical education lesson. Balance training program as an effort to prevent the occurrence of the injury shown to reduce postural sway, increase muscle strength and improve balance strategy. The objectives of the research was to assess the effect of Vladimir Janda balance training method against the risk of injury to the male students at SMP Negeri 15 Medan, Indonesia. The research used quasi-experimental study with nonrandomized control group pretest posttest design. The subjects were male students aged 12-15 years who follow basketball extracurricular. Each group consisted 11 male students. Subject exercise basketball 2 times a week for 50 minutes. Vladimir Janda balance training method performed for 5 weeks and consists of 5 phases. Phase I- IV carried out 5 times a week, while Phase V is done 3 times a week and each session lasted 10 minutes. Postural sway measured by posturometer. Body part discomfort was measured by Nordic Body Map (NBM) questionnaires. The statistical test used was the Independent t-test. There is a decrease in the frequency of postural sway of the right foot(61%) between exercise and control group, musculoskeletal pain has decreased but not statistically significant.